ŋ-Assimilation in Voice Dental Velar Voice Sound in Papuan Malay - Renhoard, Nathalia; Mahdi, Sutiono (LPPM Universitas Pancasakti Tegal, 2017)
This paper is meant to discuss correct phonological solutions to assimilation segment at the underlying level of accent in Papuan Malay. The methodology: to explain for ŋ-assimilation in Papuan Malay, the researcher refers to Halle (2017) theoretical views on Generative Phonology. The ŋ-sound appears in Papuan Malay, if a word is ended by a consonant /n/ dental velar voice results the process of ŋ-sound in the environment of cluster in the word-middle and word finally (the tow core of syllablles) and also after vowel. One example, word Teminabuan [tɛminɑbuɑn] (one of village in Papua) is uttered as Teminabuang [tɛminɑbuɑŋ].The conclusions: it is explicit that the ŋ-assimilation are not only syntactically motivated due such as a phrasal to the occurrence of a word entity in the structure but also phonologically, a word may because there are certain specific environments in which such process take place.Key Words: Phonological rules, ŋ-assimilation, Papuan Malay.